An analytical study of the National Trades Union Congress co-operative ventures in Singapore. - Foo, Yee Shoon. (2009)
The ability of NTUC co-operatives to operate successfully in a highly competitive modem market economy, whilst at the same time retaining their social function of helping to improve workers' welfare, can serve as a useful reference point for trade unions of developing countries interested in using co-operatives as a means of achieving economic and social development This thesis attempts to analyse the factors contributing to the success of NTUC co-operatives, and their contributions to the labour movement and the society at large.